Polysaccharides from Pseudostellaria heterophylla modulate gut microbiota and alleviate syndrome of spleen deficiency in rats - Qing Xiao; Li Zhao; Chang Jiang; Yanjin Zhu; Jizhou Zhang; Juan Hu; Guozeng Wang (Scientific Reports, 2022)
Abstract Pseudostellaria heterophylla, also called Tai-zi-shen (TZS) in Traditional Chinese Medicine (TCM), is always used clinically to treat spleen deficiency symptoms. Polysaccharides in TZS have various pharmacological activities, including anti-diabetic, immune regulation, and myocardial protection. However, the relationship between the spleen-invigorating effects of TZS or its polysaccharides and intestinal flora are not clear. This study investigated the effects of TZS decoction (PHD) and polysaccharide (PHP) on immune function and intestinal flora in a rat model of spleen deficiency syndrome (SDS) induced by a decoction of raw rhubarb (RRD). PHD and PHP increased immune organ index, alleviated inflammatory cell filtration, and reduced the levels of pro-inflammatory cytokines in rats with spleen deficiency syndrome. In addition, the production of butyric acid was promoted in PHD and PHP groups. Moreover, 16S rRNA gene sequencing showed that PHD and PHP reduced the relative abundance of Firmicutes while increasing the one of Bacteroidetes; significantly increased the abundance of Lactobacillus and decreased the abundance of Rombutsia; and PHP significantly increased the abundance of Alloprevotella. And there was a significant positive correlation between the alleviation of SDS and short-chain fatty acids (SCFAs)-producing bacteria. These findings suggested PHD and PHP, especially PHP, has a potential to relieve spleen deficiency by reducing intestinal inflammation, modulating structure and composition of gut microbiota, and promoting the production of butyric acid.